Evaluation Model of Non-Monetary Compensation in Management Accounting Using a Qualitative Approach - Moharrami, Ahmad; Pakmaram, Asgar; Rezaei, Nader; Abdi, Rasoul (Management Strategies and Engineering Sciences, 2025)
The aim of this study was to present a model for evaluating the value of non-monetary compensation in Management accounting using a qualitative approach based on the Grounded theory method. The data collection tool was semi-structured interviews with experts. To this end, in the qualitative phase during 2022, using a purposive (snowball) sampling approach, in-depth interviews were conducted with 13 experts who were knowledgeable and experienced in management accounting until data saturation was reached. The collected data were analyzed using a coding method with the aid of MAXQDA software. Based on the proposed model, the findings showed that regarding causal conditions, most experts in the field of Behavioral management accounting believed that the most influential factors affecting non-monetary compensation in behavioral management accounting were components such as phases of psychological–social motivation, including social norms and priorities, Cognitive psychology, and Motivational psychology. The core category of this study was non-monetary compensation in management accounting at the individual, group, and environmental levels. Two main categories—Agile management and the effects of management accounting techniques—constituted the contextual conditions. The intervening conditions consisted of two main categories: behavioral and social skills, and foundational concepts of behavioral management accounting. The first category of intervening conditions, behavioral and social skills, included the subcategories of leadership skills, teamwork, accountability, goal-setting ability, and networking skills. The category of foundational concepts of behavioral management accounting included the budgeting process, performance management, and information and decision-making. The only main strategic category was the principles of behavioral management accounting, which included five subcategories: stewardship, trust, value, relevance, and degree of influence.